Analisis Kinerja Campuran Panas Open Graded Friction Course (OGFC) Menggunakan Asbuton Murni Dengan Modifier Elvaloy (PG 82) - Siti Nuriskha Amalia; Eri Susanto Hariyadi; Nasuhi Zain (Jurnal Teknik Sipil, 2025)
Abstract This study aims to evaluate the performance of Open Graded Friction Course (OGFC) mixtures using Asbuton Murni modified with Elvaloy polymer (PG 82). The research focuses on analyzing asphalt binder characteristics and assessing the resistance of the mixture to functional distress (raveling) and structural distress (rutting and fatigue). The optimum asphalt content was determined in accordance with ASTM D7064/D7064M-08 through Void in Mix (VIM), Cantabro Loss, and draindown tests. Furthermore, the mixture performance was evaluated using Indirect Tensile Fatigue Test (ITFT) and Hamburg Wheel Tracking Device (HWTD) tests. The test results indicate that the G/sin δ* value increased from 77.5 °C to 84.5 °C, signifying improved resistance to permanent deformation. In addition, the mixing and compaction temperatures decreased, thereby enhancing the workability of the mixture. The OGFC Asbuton–Elvaloy mixture satisfied the requirements for raveling resistance and exhibited a high dynamic stability of 37,526 passes/mm, exceeding the specifications of Bina Marga. However, the fatigue performance remained relatively low, with fatigue lives of 25,186 cycles at 250 kPa and 3,375 cycles at 400 kPa. These findings demonstrate that the OGFC Asbuton–Elvaloy mixture performs well in terms of resistance to permanent deformation but has not yet fully met the criteria for a structural pavement layer. Therefore, this study recommends further development of the OGFC Asbuton–Elvaloy mixture so that it may function not only as a functional layer, but also has the potential to be developed as a structural pavement layer, with performance comparable to Bina Marga (2018) specifications for AC-WC and SMA pavements.. Keywords : Asbuton murni, Elvaloy, OGFC, VIM, Cantabro, asphalt draindown, fatigue, HWTD, rutting, dynamic stability.